Initial increase in glucose variability during Ramadan fasting in non-insulin-treated patients with diabetes type 2 using continuous glucose monitoring. Issue 1 (1st January 2019) - Aldawi, Nesreen; Darwiche, Gassan; Abusnana, Salah; Elbagir, Murtada; Elgzyri, Targ
ABSTRACT: There are no studies evaluating the glucose variability in different periods of Ramadan fasting in patients with type 2 diabetes using continuous glucose monitoring (CGM). This study examined the effect of Ramadan fasting on interstitial glucose (IG) variability in early, - late-, and post-Ramadan compared to pre-Ramadan days in non-insulin-treated type 2 diabetes patients. Participants had a CGM system connected 2 or 3 days before Ramadan start, which was removed on the third or fourth day of Ramadan. CGM performance continued for a total of 6 days. A second CGM performance started on the 27th or 28th day of Ramadan and ended on the 4th or 5th post-Ramadan day. First, CGM recordings were divided into pre-Ramadan and early-Ramadan CGM, and second recordings into late-Ramadan and post-Ramadan. At each visit, blood pressure, body weight, and waist circumference were measured, and fasting blood samples were collected for HbA1c and plasma glucose. All patients received recommended Ramadan education before Ramadan. Thirty-three patients (mean age 55.0 ± 9.8 years, 73% males) were prospectively included. IG variability, estimated as mean amplitude of glycaemic excursions (MAGE), increased significantly in early-Ramadan compared to pre-Ramadan ( P = 0.006) but not in late-Ramadan and post-Ramadan recording days. Only patients on >2 anti-diabetic drugs ( n = 16, P = 0.019) and those on sulphonylureas ( n = 14, P = 0.003) showed significant increase in MAGE in early-Ramadan. No significant changes were seen in coefficient of variation, time in range, time in hyperglycaemia, or time in hypoglycaemia. Except for an initial increase in glucose variability, fasting Ramadan for patients with non-insulin-treated type 2 diabetes did not cause any significant changes in glucose variability or time in hypoglycaemia during CGM recording days compared to non-fasting pre-Ramadan period.